Peran Otoritas Jasa Keuangan Dalam Pencegahan Fintech Illegal di Masyarakat - Fahmi Firmansyah; Maulida Dwi Kartikasari; Makmur Sujarwo; Teguh Budi Raharjo; Dien Noviany Rahmatika (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
Technological advances have an impact on aspects of life. The emergence of technological finance in online loans makes it easy to get the desired funds in a short and easy process. There are many cases of illegal fintech that we can see in national and international media. One example is the case of the VLoan application owned by PT Vcard Technology Indonesia. The purpose of this research is to see and analyze the role of the Financial Services Authority in preventing illegal activities in society, because the rampant illegal fintech in society is certainly detrimental to several parties. This research uses qualitative research with high-performance qualitative analysis application tools, namely NVivo 12. Based on the research results, the role of the Financial Services Authority in preventing illegal fintech by means of education and socialization has been effective. Obstacles in preventing illegal fintech, namely the low level of public understanding of online loans, low levels of financial literacy. This research is also expected to be a relevant source for the future. Keyword: Finansial Teknologi Illegal, Otoritas Jasa Keuangan, Pencegahan Fraud